Randomised controlled trial in pelvic floor muscle exercise intervention on urinary incontinence among pregnant women - Alagirisamy, Parwathi (2020)
Across Malaysia, despite an increased prevalence of urinary incontinence during pregnancy between 34% and 85% over the past five years, the awareness and practice of pelvic floor muscle exercise (PFME) in the prevention and reduction of urinary incontinence (UI) among pregnant women was considerably poor. This requires substantial, and urgent attention to promote continence health in the antenatal phase of a woman's life. The objective of this study was to develop, implement and evaluate the effectiveness of PFME intervention based on health belief models and motivational interviewing, focused on improving knowledge, attitude, practice and self efficacy relating to PFME, continence status and severity of urinary symptoms amongst pregnant women. A single blinded two-armed randomised control trial was conducted in the Maternity Hospital of Kuala Lumpur. A hundred and seventy eligible pregnant women at 18-20 weeks gestation with or without urinary incontinence were randomly assigned into intervention and control group by using a computer-generated stratified permuted block size of 6 for each combination of the continence status and parity. In addition to usual perinatal care, the intervention group received PFME intervention which consists of one group session of PFME education followed by three booster sessions at 4 weeks post-intervention, early, and late third trimester of pregnancy together with weekly text message reminders for 8 weeks. Whereas, the control group received the usual perinatal care. The data were collected at 4 time points; baseline, post intervention at early third trimester, late third trimester and early postnatal. Socio-demographic and clinical characteristics as well as primary and secondary outcome measurements were taken using validated questionnaires; Knowledge Attitude Practice of PFME questionnaire, Self-Efficacy Scale for Practicing Pelvic Floor Exercises and the International Consultation on Incontinence Questionnaire-Urinary Incontinence-Short Form. Data were analyzed using SPSS Statistics 22 and the significant level set at alpha=0.05. The intervention effects were analyzed using a generalized estimating equation. The primary analysis was based on modified intention-totreat including respondents with at least 1 follow-up, pursued with an intentionto- treat sensitivity analysis. Among the 170 respondents at baseline, 112 (65.9%) returned for their early third trimester follow-up visit, 82 (48.2%) returned for their late third trimester follow-up and only 21 (12.4%) returned for their early postnatal follow-up. At baseline, there were no significant differences in socio-demographics and characteristics of the respondents between intervention and control group. The results of primary analysis, which includes 122 respondents show that the intervention group had a significant improvement in knowledge (Wald X²=59.571, p<0.001), attitude (Wald X²=19.164, p<0.001), practice (Wald X² =58.113, p<0.001) and self-efficacy (Wald X²=90.045, p<0.001) over time compared to the control. However, there was no significant improvement in self-reported urinary incontinence (Wald X²=3.369, p=0.338) but the severity of urinary incontinence was significantly reduced over time among the intervention group compared to control group (Wald X²=25.904 p<0.001). The results of this study indicate that PFME intervention could be considered as an initial offering in providing information about urinary incontinence prevention to pregnant women.